Pervasive supply of therapeutic lysosomal enzymes in the CNS of normal and Krabbe‐affected non‐human primates by intracerebral lentiviral gene therapy. Issue 5 (29th March 2016) - Meneghini, Vasco; Lattanzi, Annalisa; Tiradani, Luigi; Bravo, Gabriele; Morena, Francesco; Sanvito, Francesca; Calabria, Andrea; Bringas, John; Fisher‐Perkins, Jeanne M; Dufour, Jason P; Baker, Kate C; Doglioni, Claudio; et al.
Abstract: Metachromatic leukodystrophy (MLD) and globoid cell leukodystrophy (GLD or Krabbe disease) are severe neurodegenerative lysosomal storage diseases (LSD) caused by arylsulfatase A (ARSA) and galactosylceramidase (GALC) deficiency, respectively. Our previous studies established lentiviral gene therapy (GT) as a rapid and effective intervention to provide pervasive supply of therapeutic lysosomal enzymes in CNS tissues of MLD and GLD mice. Here, we investigated whether this strategy is similarly effective in juvenile non‐human primates (NHP). To provide proof of principle for tolerability and biological efficacy of the strategy, we established a comprehensive study in normal NHP delivering a clinically relevant lentiviral vector encoding for the human ARSA transgene. Then, we injected a lentiviral vector coding for the human GALC transgene in Krabbe‐affected rhesus macaques, evaluating for the first time the therapeutic potential of lentiviral GT in this unique LSD model. We showed favorable safety profile and consistent pattern of LV transduction and enzyme biodistribution in the two models, supporting the robustness of the proposed GT platform. We documented moderate inflammation at the injection sites, mild immune response to vector particles in few treated animals, no indication of immune response against transgenic products, and no molecular evidence of insertional genotoxicity. Efficient gene transfer in neurons, astrocytes, and oligodendrocytes close to the injection sites resulted in robust production and extensive spreading of transgenic enzymes in the whole CNS and in CSF, leading to supraphysiological ARSA activity in normal NHP and close to physiological GALC activity in the Krabbe NHP, in which biological efficacy was associated with preliminary indication of therapeutic benefit. These results support the rationale for the clinical translation of intracerebral lentiviral GT to address CNS pathology in MLD, GLD, and other neurodegenerative LSD. Synopsis: Report on the safety and efficacy of clinically relevant intracerebral gene therapy to deliver lysosomal enzymes in non‐human primates (NHP) and first evidence of efficacy in a Krabbe‐affected NHP recapitulating human globoid cell leukodystrophy. Two intracerebral injections of low doses of therapeutic lentiviral vectors (LV.hARSA, LV.hGALC) performed in juvenile NHP (to mimic the potential treatment of infantile/early juvenile patients) were well tolerated, with undetectable immune response or genotoxicity related to LV integration. Efficient gene transfer and transgene expression were observed in oligodendrocytes (in addition to neurons and astrocytes), which are hardly transduced by other vector types. Stable and widespread supraphysiological and close to physiological enzymatic activities were measured in normal animals and in the Krabbe‐affected NHP, respectively. Neurobehavioral assessment showed a progressive increase of motor scores in the LV.hGALC‐treated Krabbe NHP, with values close to the mean observed in normal animals at 3 months post‐gene therapy. The extent of ARSA and GALC activity in CNS tissues post‐gene therapy is expected to provide benefit if achieved in human patients, since ≈ 10% of physiological enzymatic activity would ensure a normal phenotype. Abstract : Report on the safety and efficacy of clinically relevant intracerebral gene therapy to deliver lysosomal enzymes in non‐human primates (NHP) and first evidence of efficacy in a Krabbe‐affected NHP recapitulating human globoid cell leukodystrophy.